Gamification in School Education: A Systematic Review of Its Effectiveness in Improving Student Motivation and Academic Outcomes - Nurhayati Nurhayati; Fathurrohman Fathurrohman (STAI Hubbulwathan Duri, 2025)
The integration of technology in education has led to the growing adoption of gamification as a tool to enhance student engagement, motivation, and academic achievement. Despite its benefits, concerns remain regarding its impact on deep learning and disparities in technological access among institutions. This study conducted a systematic literature review to assess the effects of gamification on student motivation and learning outcomes across educational levels. Guided by the PRISMA framework, 278 articles were initially retrieved from the Scopus and ERIC databases. After screening and quality assessment, 21 peer-reviewed studies published between 2021 and 2024 were included, with quality scores ranging from 60% to 100% (average 82%). Findings indicate that gamification positively influences student motivation and often enhances academic performance, especially in primary and secondary education. The most effective game elements identified were points, badges, leaderboards, progress tracking, real-time feedback, collaboration, real-world applications, and autonomy support. However, the effectiveness of gamification varies depending on subject matter, educational stage, and technological infrastructure. While gamification offers notable benefits, its impact is context-dependent. To maximize its potential, educators must adopt balanced approaches that consider student needs, curricular goals, and available resources. Gamification can significantly enhance student learning and motivation when implemented strategically and supported by robust pedagogical and technological frameworks.